Taxonomic and natural history notes on Oecomys cleberi (Rodentia: Cricetidae) and first records in the Atlantic Forest, Brazil - Brandão, Marcus Vinicius; Garbino, Guilherme Siniciato Terra; Rezende, Gabriela Cabral [UNESP]; Tenório, Simone Fraga; Reis, Sarah Fontes (Taylor & Francis, 2022)
The arboreal rodent Oecomys cleberi was previously considered endemic to the Cerrado domain in central-western Brazil. We report on a range extension of O. cleberi to the Atlantic Forest domain of São Paulo, and add new records to Mato Grosso do Sul and Minas Gerais states, totaling 10 new records. Based on a large sample of O. cleberi, we did not find evidence for sexual dimorphism. Our results revealed that specimens of O. cleberi from Cerrado and Atlantic Forest are larger than O. bicolor from the Amazon. Moreover, the larger buccinator–masticatory/foramen ovale confluence in O. cleberi allowed further distinction to O. bicolor. We also provide further details of morphological variation within O. cleberi. Reproductive males and females of O. cleberi were recorded in the rainy season, between December and January, and one male was infested by the mite Gigantolaelaps canestrinii. Our new records show that this arboreal rodent is also present in seasonal forests within the domain of the Atlantic Forest. We suggest that this species, typical of the Cerrado, occurs only marginally in the Atlantic Forest of São Paulo.
Keywords: Arboreal Rice rat; Cerrado; Morro do Diabo State Park; Oryzomyini; Pontal do Paranapanema